Longitudinal in vivo Ca2+ imaging reveals dynamic activity changes of diseased retinal ganglion cells at the single-cell level - Li, Liang; Feng, Xue; Fang, Fang; Miller, David A.; Zhang, Shaobo; Zhuang, Pei; Huang, Haoliang; Liu, Pingting; Liu, Junting; Sredar, Nripun; Liu, Liang; Sun, Yang; et al. (Proceedings of the National Academy of Sciences - PNAS, 2022)
Retinal ganglion cells (RGCs) are heterogeneous projection neurons that convey distinct visual features from the retina to brain. Here, we present a high-throughput in vivo RGC activity assay in response to light stimulation using noninvasive Ca2+ imaging of thousands of RGCs simultaneously in living mice. Population and single-cell analyses of longitudinal RGC Ca2+ imaging reveal distinct functional responses of RGCs and unprecedented individual RGC activity conversions during traumatic and glaucomatous degeneration. This study establishes a foundation for future in vivo RGC function classifications and longitudinal activity evaluations using more advanced imaging techniques and visual stimuli under normal, disease, and neural repair conditions. These analyses can be performed at both the population and single-cell levels using temporal and spatial information, which will be invaluable for understanding RGC pathophysiology and identifying functional biomarkers for diverse optic neuropathies.